Feasibility study of cement-treated 0–8 mm recycled aggregates from construction and demolition waste as road base layer. Issue 3 (2nd July 2016) - Del Rey, I.; Ayuso, J.; Barbudo, A.; Galvín, A.P.; Agrela, F.; de Brito, J.
Abstract : Recently, both nationally and internationally, cement-treated granular materials (CTGMs) have been widely used as road base layer. However, all the researches on CTGM with recycled aggregates (RA) are limited to the coarse fraction, with a size range of 0–40 mm. In Spain, one of the recycled materials most commonly produced in construction and demolition waste (CDW) treatment plants is a mixture with around 75% of fine recycled aggregates (hereby called FRA), with 5–8 mm nominal maximum size. This material is commonly used in pipe bedding, an application that provides little or no added-value. The intent of this paper is to study the feasibility of using CTGM made with FRA as road base layer. For this purpose, six mixtures have been produced, comprising 0–8 mm FRA and 0–40 mm coarse aggregates, made of mixed recycled aggregates and recycled concrete aggregate. The main mechanical (unconfined compressive strength and modulus of elasticity) and durability (dimensional changes) properties were studied and the effects of size and aggregates' source were analysed. To the best of the authors' knowledge, this is the first study on the use of the fine fraction of CDW in the production of CTGM to be used as road base layer. It suggests that it is feasible to produce CTGM with 0–8 mm RA (SC20) from CDW for that purpose. In addition, CTGM with FRA have better mechanical properties and dimensional changes than CTGM with coarse recycled aggregates (SC40).